Debonding characteristics and strengthening mechanics of all-CFRP sandwich beams with interface-reinforced honeycomb cores. (8th February 2022) - Wei, Xingyu; Xue, Pengcheng; Wu, Qianqian; Wang, Yan; Xiong, Jian
Abstract: The weakest link in traditional sandwich beams constructed of carbon fiber reinforced polymer (CFRP) honeycomb core is arguably the bonded face sheet-core interface. This has limited the development and the expanded application of these sandwich structures. To overcome this, in this paper, a type of interface-reinforced honeycomb core is proposed to improve the bonding by enlarging the bonding area and thus increasing the strength of the face sheet-to-core attachment. A modified tailor-folding method is employed to fabricate two designs of the interface-reinforced honeycomb. The two interfaces reinforced cores are identical, except for the presence of machined holes in the strengthened fillet created to accommodate adhesive fillets formed during bonding. Double cantilever beam (DCB) test is performed to compare the bonding and behavior of the beams, which are tested alongside beams of a traditional honeycomb that is used as a control sample. In addition, the influences of cell wall thickness and loading direction with respect to the orientation of core macrostructures are also investigated. Modified Beam Theory (MBT) and Elastic Foundation Model (EFM) are employed to calculate the critical strain energy release rate. Overall, the interfaced-reinforced cores performed much better than the traditional core, with the former and latter being stronger in the transverse and longitudinal directions, respectively. The various failure modes observed from the test are analyzed and used to illustrate the strengthening mechanics operating in the interface-reinforced honeycomb. Graphical abstract: Image 1 Highlights: Two designs of an interface-reinforced honeycomb are proposed and investigated by the DCB method. The fabrication process employed to fabricate the honeycomb cores is a modified tailor-folding method. The influences of cell wall thickness and loading direction are also investigated. The strain energy release rates G is calculated from the modified beam theory and elastic foundation model. The debonding characteristics and strengthening mechanics are analyzed by studying the failure modes.